2013
DOI: 10.5665/sleep.2308
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Heart Rate Response is Associated with Hypocretin Deficiency in Patients with Narcolepsy

Abstract: Our results show that autonomic dysfunction is part of the narcoleptic phenotype, and that hypocretin-1 deficiency is the primary predictor of this dysfunction. This finding suggests that the hypocretin system participates in the modulation of cardiovascular function at rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
2
32
1
Order By: Relevance
“…Nonetheless, an attenuated HR response to PLMS was observed in 14 NT1 patients suggesting a lower sympathetic response related to hypocretin-deficiency [124]. Similar results were obtained in NT1 in relation to leg movements and arousal from sleep defined according to standard criteria [125][126][127]. The attenuated HR response was primarily predicted by hypocretin-deficiency.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Nonetheless, an attenuated HR response to PLMS was observed in 14 NT1 patients suggesting a lower sympathetic response related to hypocretin-deficiency [124]. Similar results were obtained in NT1 in relation to leg movements and arousal from sleep defined according to standard criteria [125][126][127]. The attenuated HR response was primarily predicted by hypocretin-deficiency.…”
supporting
confidence: 78%
“…The attenuated HR response was primarily predicted by hypocretin-deficiency. However the baseline HR values during sleep of the NT1 group in this study [125] were significantly elevated compared with controls, suggesting that the attenuated phasic HR increase may also be explained by the already elevated basal HR values resulting from a tonic sympathetic prevalence during sleep.…”
contrasting
confidence: 58%
“…Orexin neuron inactivation, in turn, may lead to diminished cardioprotective parasympathetic activity from CVNs to the heart. Supporting this hypothesis, individuals with narcolepsy, the disease characterized by orexin neurons deficiency, have increased heart rate during wakefulness (Grimaldi et al, 2012, Sorensen et al, 2013). Similar, tachycardia has been reported in orexin-deficient mice (Bastianini et al, 2011, Silvani et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in which heart rate variability was measured in patients with narcolepsy have demonstrated normal reduction in sympathetic outflow during sleep, but reduced parasympathetic tone during wakefulness (Ferini-Strambi et al, 1997) or enhanced sympathetic activity during orthostatic stress (Grimaldi et al, 2010b). Baseline heart rate has also been reported to be elevated in narcolepsy (Grimaldi et al, 2012; Sorensen et al, 2013). The normal responses of increased heart rate in relation to arousals from sleep and decreased blood pressure during sleep have been shown to be blunted in narcolepsy with cataplexy (Dauvilliers et al, 2012; Grimaldi et al, 2012), particularly in those patients with low or absent HCRT1, even compared to narcolepsy patients with normal HCRT1 levels (Sorensen et al, 2013).…”
Section: Overview Of Narcolepsymentioning
confidence: 99%
“…Baseline heart rate has also been reported to be elevated in narcolepsy (Grimaldi et al, 2012; Sorensen et al, 2013). The normal responses of increased heart rate in relation to arousals from sleep and decreased blood pressure during sleep have been shown to be blunted in narcolepsy with cataplexy (Dauvilliers et al, 2012; Grimaldi et al, 2012), particularly in those patients with low or absent HCRT1, even compared to narcolepsy patients with normal HCRT1 levels (Sorensen et al, 2013). Together, these results support the hypothesis that HCRT insufficiency, concomitant with altered sleep architecture, leads to increased sympathetic activation.…”
Section: Overview Of Narcolepsymentioning
confidence: 99%